Vermikompos Penghasil Biomassa Cacing Tanah (Lumbricus rubellus) Dan Cacing Kalung Serta Kompos Dengan Metode Budidaya Efektif - Faroh, Ahmad Nailul; Solichin, Mochammad; Pratama, Try Andreas Ilham Putra (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Earthworm Lumbricus rubellus and worms necklace have many advantages likes easy maintenance management, short production cycle, benefit many sectors, as well as market demand and current earthworms prices. The aim of earthworm farming were creating new business opportunities with relatively little capital, and developing entrepreneurial spirit of students. Earthworms cultivated with a medium of cow manure that have halfly decomposed. Effective method of cultivation was done for increasing the production of earthworms, preventing of seeds deficiency, and simplifying of harvesting method. Cultivation begun with preparation of the cage, growing medium of worms, earthworms starter purchasing. After that, the market survey was done by approaching the farmer store, bait shop, the seller of ornamental plants and other earthworms farmer. It was done to determine the product marketing opportunities and the right marketing strategy. Then the products were sold to the stores that had been surveyed before. Proceeds from saling the products that had achieved from earthworms was around 123 kg, 480 pcs of vermicompost, and 20 liters of liquid fertilizer. Total income earned up to Rp 13.295.000.00. The value of R / C ratio was 1.56 effort. This value indicated that the business was viable. Keywords : Earthworms, Marketing, Product